2020
DOI: 10.2147/opth.s227670
|View full text |Cite
|
Sign up to set email alerts
|

<p>Implantation of a Trifocal Intraocular Lens in High Myopic Eyes with Nasal-Inferior Staphyloma</p>

Abstract: Purpose: To assess visual outcomes in high myopic eyes with nasal-inferior staphyloma implanted with a pseudophakic trifocal intraocular lens (IOL). Methods: We retrospectively analyzed the visual outcomes of 50 eyes of 45 patients who had cataract surgery after AT LISA trifocal IOL implantation. Twenty-five eyes diagnosed with posterior staphyloma (nasal-inferior, type IV and V), and 25 eyes as long eyes. Uncorrected distance visual acuity (UDVA) and corrected distance visual acuity (CDVA) values were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…The present findings suggest that even highly myopic cases seem to present no significant difference in axial length, depending on the subclassification of PS evaluated by wide-field fundus imaging. The present findings are consistent with those of previous studies on eyes with high myopia and PS ( 30 ), showing that refractive outcomes vary significantly among different types of PS after cataract surgery. In addition, a significant correlation between posterior staphyloma classification and postoperative RE was observed.…”
Section: Discussionsupporting
confidence: 93%
“…The present findings suggest that even highly myopic cases seem to present no significant difference in axial length, depending on the subclassification of PS evaluated by wide-field fundus imaging. The present findings are consistent with those of previous studies on eyes with high myopia and PS ( 30 ), showing that refractive outcomes vary significantly among different types of PS after cataract surgery. In addition, a significant correlation between posterior staphyloma classification and postoperative RE was observed.…”
Section: Discussionsupporting
confidence: 93%
“…In summary, it was shown that the aspheric-enhanced MIOL provided good distance visual acuity while the trifocal diffractive IOL provided good intermediate visual acuity in patients with post-LASIK cataract. Furthermore, the outcomes of the present study [ 32 ] show that a trifocal IOL(AT LISA tri 839 MP) provides good visual acuity in high myopic eyes, being worse for nasal-inferior staphyloma eyes. Whether such patients with a history of LASIK have additional visual acuity effects after trifocal IOL implantation has not been reported.…”
Section: Visual Acuitymentioning
confidence: 69%
“…However, the severity of a posterior staphyloma can vary and does not completely exclude a patient from a MfIOL but should cause hesitation in the surgeon. One study examining extreme myopes with and without staphylomas for AT LISA trifocal IOL (Carl Zeiss, Meditec) implantation found superior visual outcomes in eyes without a staphyloma [ 11 ]. Corrective distance acuity was 0.91 and 0.74 for the negative versus positive staphyloma group, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Corrective distance acuity was 0.91 and 0.74 for the negative versus positive staphyloma group, respectively. Specifically, nasal-inferior macula staphyloma with higher macula plane tilt (>30 degrees) showed worse outcomes [ 11 ].…”
Section: Discussionmentioning
confidence: 99%